Tour Cloud Mobile: Helping Tourists Acquire the Information Effectively Using Three Types of Views - Kim, Jungbin; Ko, Heedong; Yoo, Byounghyun (2015 IEEE INTERNATIONAL CONFERENCE ON CONSUMER ELECTRONICS (ICCE), 2015)
This paper presents a mobile application that helps tourists acquire information using three types of views AR, map, and list view each of which has different drawbacks and benefits. To deal with the disadvantages of each view, we propose a view-management component to change the layout depending on the context.